Effects of Side Strap and Elastic Hems of Bra Materials on Clothing Pressure Comfort (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper, a new approach has been developed to create virtual dress based on different body types. A3D scan data of 232 Chinese females were analyzed. Firstly, samples were classified into four categorieswhich were Torso Volume Index (TVI), slender, average, full and heavy. Secondly, 3D body frame,including 10 feature cross-sections extracted from the scan data, was defined and preprocessed. Afterthat, the average data of 3D body frame in each body type group was calculated and a comparativeanalysis of the feature measurements among the four average body frames was performed. Finally, ashape deformation algorithm was presented to modify the template model according to four average bodyframes. And surface fitting is implemented by using NURBS technology. In conclusion, the research hascreated four mannequins representing the average body shape of each group subjects. The results cancontribute to the future study on customizing digital mannequins for 3D virtual apparel design system,according to the body shape of target population.
Keywords: 3D Scan Data; Virtual Dress Form; Body Shape Classification; Shape Deformation